Encapsulation of enzymes into nanogel and associated degradation of phenolic compounds - WU Wugao; ZHANG Wang; CHEN Yantao (Shenzhen Daxue xuebao. Ligong ban)
As an effective means of degradation of phenolic pollutants, peroxidase exhibits high catalytic activity but poor environmental tolerance, and it is difficult to be widely used in sewage treatment. In order to enhance the environmental tolerance of horseradish peroxidase (HRP) and be used for phenol degradation, the modified horseradish peroxidase (HRP) was gelatinized and embedded in gel and acryloylated through the amino or carboxyl groups on the surface of HRP, and two encapsulated enzymes (n-HRP@PAM, c-HRP@PAM) were prepared by in situ free radical polymerization reaction with acrylamide (AAm). Mass spectrometry revealed that up to nine double bonds could be grafted on the carboxyl groups of HRP, and more than the number of double bonds grafted on its amino groups. Dynamic laser scattering showed that the two encapsulated enzymes were uniformly dispersed in aqueous solution. Furthermore, the enzymatic activity and thermal stability of two encapsulated enzymes were explored with the colorimetric reaction of tetramethylbenzidine, and the influence of HRP concentration and hydrogen peroxide on the degradation of phenolic compounds was studied. The environmental tolerance and recycling performance of natural HRP and two encapsulated enzymes were compared. Results show that, compared with natural HRP and n-HRP@PAM, c-HRP@PAM has a denser polymeric network, higher thermal stability and environmental tolerance, and the best degradation effect on phenolic wastewater. Overall, this study proves that acrylation of carboxyl groups on the peroxidase surface and the in situ preparation of nanogel are an effective way to improve the environmental tolerance of enzyme.